Cladocera from the Sediment of High Arctic Lake in Svalbard (Norway) - Singh Vartika (Sciendo, 2021)
The High Arctic Region’s freshwater ecosystems serve as hot spots to study the impact of extreme warming conditions on the biota. The cladoceran remains have been recovered from the surface sediments of a non-marine water body near Ny-Alesund, Svalbard, Norway. The cladoceran (crustaceans) belongs to the Chydorus sphaericus group Frey, 1980 and Daphnia pulex Leydig, 1860. The ecology of the species suggests that they lived in a well-developed ecosystem with Water Quality Class 3. This study has implications for understanding the response of the present-day biota experiencing the changing climate conditions and using these remains for assessing palaeoenvironmental conditions.